Influence of family management in corporate boards on firm value - Cheng, Ming Qi (Nanyang Technological University, 2008)
This paper aims to investigate whether family members in the board will negatively influence firm value when there is evidence of wealth expropriation from minority shareholders. The hypotheses were tested using a sample of 286 publicly-listed firms on the Singapore Stock Exchange, and the results largely support our arguments. Specifically, we found that the proportion of family members in corporate boards is negatively associated with Tobin’s Q, and that the relationship is more negative when SG&A expenses are higher. Finally, implications for research and practice are discussed.